Strengthening External Emergency Assistance for Managing Extreme Events, Systemic, and Transboundary Risks in Asia - Prabhakar, Sivapuram Venkata Rama Krishna (2021)
External emergency assistance (EEA) provided in the aftermath of a disaster has costs and benefits to the donor and recipient countries. Donors benefit from quick recovery feedback effects from the trade and cultural links, and recipient countries have additional resources to manage the emergency. However, EEA costs could outweigh the benefits. Costs include dependency, low development of risk reduction capacity, and staff burdened with managing the assistance as opposed to managing the recovery. Current efforts to reduce dependency on EEA are not sufficient; they are based on limited past experiences with extreme events and are not based on the understanding of future risks. In this article, we present the concept of a climate fragility risk index showing factors that affect a country’s predisposition to be fragile to climate change threats and we suggest that countries with a high climate fragility risk index tend to depend on EEA. Further, the article presents the concept of critical thresholds for extreme events as a metric to identify possible dependency on EEA. In addition, based on expert and policy consultations organized in the Philippines and Pakistan, we identify measures that can enhance the effectiveness of EEA including targeted EEA provision, better integration of lessons learned from the relief stage into the rest of the DRR operations, proper documentation of past assistance experiences and consideration of these lessons for the improvement of EEA in the future, as well as developing tools such as critical threshold concepts that can better guide the donor and recipient countries on more effective delivery of EEA.